Building up the first continents: Mesoarchean to Paleoproterozoic crustal evolution in West Troms, Norway, inferred from granitoid petrology, geochemistry and zircon U-Pb/Lu-Hf isotopes - Laurent, Oscar; Vander Auwera, Jacqueline; Bingen, Bernard; Bolle, Olivier; Gerdes, Axel (Precambrian Research, 2019)
ISSN:0301-9268 ISSN:1872-7433